World energy outlook 2000 (World Energy Outlook / IEA, 2000)
This outlook, the first since the Kyoto agreement on climate change, analyses the major issues and uncertainties of the global energy scene from now till the year 2020. Te outlook examines the emissions-cutting commitments made at Kyoto amd points out that they will be impossible to meet if governments continue to treat energy on a "business as usual" basis. Hence, a whole new policy-mix- including regulations, flexible market mechanisms and the encourangement of less polluting sources such as renewable energy anf nuclear power- will be required to meet the Kyoto targets. Along with its global analysis, the outlook contains separate, detailed studies of 10 regions.